2017
DOI: 10.1002/lsm.22691
|View full text |Cite
|
Sign up to set email alerts
|

Lentigo maligna melanoma with a history of cosmetic treatment: Prevalence, surgical outcomes and considerations

Abstract: Introduction Lentigo maligna (LM) is melanoma in situ on sun-damaged skin and presents diagnostic challenges due to overlapping features with benign pigmented lesions. Cosmetic treatments may be inadvertently performed on LM. The aim of this study is to estimate the prevalence of LM with prior cosmetic treatment, and evaluate surgical outcomes. Study Design and Methods Retrospective review of biopsy-proven LM presenting over a ten-year period (2006–2015). Prior cosmetic treatment and biopsies were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Little information and few high-quality studies are available on this topic. There is also an ongoing assumption that the incidence of residual or recurrent tumors is higher following non-surgical procedures [ 19 ] . A recent literature review by Read et al demonstrated mean recurrence rates of 11.5 % for radiotherapy, 24.5 % for topical imiquimod and 34.4 % for lasers after the treatment of lentigo maligna [ 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Little information and few high-quality studies are available on this topic. There is also an ongoing assumption that the incidence of residual or recurrent tumors is higher following non-surgical procedures [ 19 ] . A recent literature review by Read et al demonstrated mean recurrence rates of 11.5 % for radiotherapy, 24.5 % for topical imiquimod and 34.4 % for lasers after the treatment of lentigo maligna [ 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…When considering the possibility of misdiagnosis, we must consider the broad differential diagnosis of solar lentigines, which includes early seborrheic keratoses, pigmented actinic keratoses, and benign melanocytic nevi, as well as lentigo maligna (LM), a type of melanoma in situ [2]. As solar lentigines are a clinical diagnosis with a wide differential, whose definition may vary between physicians, it is logical that a variety of cosmetic treatments may be performed on these lesions [5]. Several reports have documented LM arising after laser therapies to a pigmented lesion [2, 5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Zu diesem Thema stehen kaum Informationen und nur wenige qualitativ hochwertige Studien zur Verfügung. Es besteht nach wie vor die Vermutung, dass die Inzidenz residualer oder rezidivierender Tumoren nach nichtchirurgischen Verfahren höher ist . Eine kürzliche Literaturübersicht von Read et al.…”
Section: Diskussionunclassified